Study of F1 car aerodynamics rear wing using computational fluid dynamic (CFD) - Mohd Shahmal, Mohd Shahid (2010)
This thesis deals with the study on the rear wing of the F1 car. This research is about the analysis of drag coefficient, and lift coefficient, using the Ansys software. The analysis consist of two cases. First case by 2D analysis and other case by using 3D analysis. The design the rear wing of formula one car, based on the FIA 2009 regulation by using Solidwork software. NACA of NACA 2312, NACA 2308 and NACA 2104 were used. The = 1.2 × 106 and = 0.147 are use in the research. 2D result obtained from the research of the NACA 2312, NACA 2308 and NACA 2104 for the drag coefficient, are in range 0.01697 until 0.04340 and for lift coefficient, are in range -0.26427 until -0.35808. 3D result for NACA 2312, NACA 2308 and NACA 2104 on drag coefficient, are in range 0.02979 until 0.04046 and lift coefficient, in range -0.00386 until -0.00434.